PENETAPAN KADAR FLAVONOID TOTAL DAN AKTIVITAS ANTIOKSIDAN EKSTRAK AKAR NIPAH (Nypa fruticans Wurmb) DENGAN METODE SPEKTROFOTOMETRI UV-Vis - Devi Oktaria; Mauritz Pandapotan Marpaung (Lantanida Journal, 2023)
Akar nipah (Nypa fruticans Wurmb) contains active chemicals in the form of flavonoids and is a component of the nipah plant with antioxidant activity. The study's goal was to determine the total flavonoid content as well as the antioxidant activity of akar nipah extract. The extraction method is a maceration method with methanol as the solvent. Total flavonoid levels in akar nipah extract were determined using UV-Vis spectrophotometry after the addition of 10% AlCl3 at a wavelength of 433 nm, while antioxidant activity was determined using the DPPH (2,2-diphenyl-1-picrylhydrazyl) technique at a wavelength of 516 nm. The total flavonoid levels and antioxidant activity were determined in comparison to quercetin. According to the study's findings, akar nipah extract contains flavonoids at 0.05 0.01% and has very strong antioxidant activity (IC50 of 6.59 ppm).